Digital therapeutics in urology: an innovative approach to patient care and management - Rodler, Severin; Kowalewski, Karl-Friedrich; Scheibert, Henriette; Bensel, Moritz; Stadelmeier, Leo Federico; Styn, Amelie; Belenchon, Ines Rivero; Taratkin, Mark; Puliatti, Stefano; Gomez Rivas, Juan; Veccia, Alessandro; Piazza, Pietro; et al. (European urology open science, 2023)
Digital therapeutics (DTx) are a new class of intervention involving evidence-based software applications and have been used in neurology and psychiatry. To assess the potential of DTx in urology, we conducted a survey to assess the current prevalence of the digital infrastructure required for DTx, areas of support expected by patients, and requirements for uptake. Between November 2022 and January 2023, we conducted an anonymized survey at two German academic centers among patients with urologic conditions. We found that among patients aged <65 yr versus ≥65 yr, digital devices including smartphones (93.6% vs 77.3%; p < 0.001), computers (80.4% vs 70.1%; p < 0.001), tablets (51.7% vs 38.1%; p < 0.001), and smartwatches (24.7% vs 7.7%; p < 0.001) are already widely used, especially in the younger age group. Apps (95.6% vs 74.4%; p < 0.001) and health apps (57.6% vs 30.4%; p < 0.001) are already frequently used, but certified DTx apps are not (7.3% vs 5.4%; p = 0.25). Patients favor solutions that provide access to validated information (49.6%), give medical advice based on data or symptoms captured by the app (43.0%), or replace a physiotherapist (41.7%). Patients feel that optimization of therapy (78.4%), significant positive health outcomes (76.9%), and better patient autonomy (73.4%) are important requirements for DTx in urology. Regulatory and reimbursement changes mean that DTx might play an increasing role in urology. - Patient summary - Patients can use digital therapeutics (DTx), which are mainly smartphone apps, to improve their health status or treat medical conditions. We assessed the current and future use of DTx in urology. Patients are already widely using smartphones and frequently use uncertified health apps, but do not use DTx. Patients would like to use DTx to optimize therapy that provides a significant health improvement.
Online verfügbar: 4. August 2023, Artikelversion: 4. August 2023
Gesehen am 18.07.2024